Gray and white matter astrocytes differ in basal metabolism but respond similarly to neuronal activity. Issue 2 (5th September 2022) - Köhler, Susanne; Winkler, Ulrike; Junge, Tabea; Lippmann, Kristina; Eilers, Jens; Hirrlinger, Johannes
Abstract: Astrocytes are a heterogeneous population of glial cells in the brain, which adapt their properties to the requirements of the local environment. Two major groups of astrocytes are protoplasmic astrocytes residing in gray matter as well as fibrous astrocytes of white matter. Here, we compared the energy metabolism of astrocytes in the cortex and corpus callosum as representative gray matter and white matter regions, in acute brain slices taking advantage of genetically encoded fluorescent nanosensors for the NADH/NAD + redox ratio and for ATP. Astrocytes of the corpus callosum presented a more reduced basal NADH/NAD + redox ratio, and a lower cytosolic concentration of ATP compared to cortical astrocytes. In cortical astrocytes, the neurotransmitter glutamate and increased extracellular concentrations of K +, typical correlates of neuronal activity, induced a more reduced NADH/NAD + redox ratio. While application of glutamate decreased [ATP], K + as well as the combination of glutamate and K + resulted in an increase of ATP levels. Strikingly, a very similar regulation of metabolism by K + and glutamate was observed in astrocytes in the corpus callosum. Finally, strong intrinsic neuronal activity provoked by application of bicuculline and withdrawal of Mg 2+ caused a shift of the NADH/NAD + redox ratio to a more reduced state as well as a slight reduction of [ATP] in gray and white matter astrocytes. In summary, the metabolism of astrocytes in cortex and corpus callosum shows distinct basal properties, but qualitatively similar responses to neuronal activity, probably reflecting the different environment and requirements of these brain regions. Main Points: Gray and white matter astrocytes have different basal NADH/NAD + redox states and ATP levels. Metabolism of both cell populations responds similarly to neuronal activity. Glutamate induced ATP loss is prevented by increasing extracellular K + .